The Masstige Strategy For Boosting Property Sales: Performance Analysis And Recommendations For Product Differentiation At PT. Neo Pudji Jaya - Setiyo Budi Tripriyono; Feti Fatimah (Universitas Dehasen Bengkulu, 2026)
Purpose: This study aims to analyze the potential of adding a variant of masstige-concept housing (2-storey houses) to increase sales for developer PT. Neo Pudji Jaya at Shaistanaya City Sidoarjo Housing, both for the masstige variant and the 1-storey house variant. Research methodology: The study uses a descriptive quantitative approach with secondary data in the form of annual sales data for the 2022–2025 period (realizations and sales targets), gap achievement analysis, and integration of Indonesian property market context data. Results: Sales realizations for 2022–2025 amounted to 145 units out of a cumulative target of 405 units (achievement 35.8%); the trend shows a peak in 2023 (64.4%) but declined sharply in 2024–2025 (30.8%–24.0%) despite continuously increasing targets, with a cumulative deficit gap of 260 units. Limitations: Data are not yet available by house type and do not yet include specific price variables, measurable promotion intensity, or prospect (leads) data, so causal proof is limited to theoretical and empirical argumentation. Contribution: The article provides managerial recommendations based on masstige literature evidence, Indonesian market segmentation, and property consumer behavior for product differentiation that can enhance area image and cross-variant sales.